Influenza A virus NS1 protein mimics oncogenic PI3K resulting in isoform specific cellular redistribution and activation - Sadaf Aslam; María T. Sánchez-Aparicio; Braden D. Siempelkamp; Gillian L. Dornan; Nikos Tsolakos; John E. Burke; Benjamin G. Hale; Adolfo García-Sastre; Juan Ayllon (Proceedings of the National Academy of Sciences, 2025)
The nonstructural protein 1 (NS1) of influenza A virus performs a broad variety of proviral activities in the infected cell, primarily mediating evasion from the host innate immune response by being the main viral interferon antagonist. However, there are several interactions whose biological relevance remains obscure, such as the ability of NS1 to bind and activate class IA phosphoinositide 3-kinases (PI3Ks). PI3Ks are highly regulated lipid kinases that act as critical nodes in multiple cell signaling networks and are also important proto-oncogenes. This activation is mediated by NS1 binding specifically to the p85β subunit. To better understand the consequences of this interaction, we developed a bimolecular fluorescence complementation (BiFC) assay to selectively track the different PI3K heterodimers and, using this system, we found that NS1 induces an isoform-specific relocation and activation of the different PI3K heterodimers. We found that clinically relevant oncogenic mutations in both catalytic and regulatory subunits of PI3K could mimic the effect caused by NS1, and partially rescue the loss of viral fitness in a recombinant virus encoding a p85β-binding deficient NS1.